2015
DOI: 10.1021/ed500945g
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the STEM Gender Gap by Designing and Implementing an Educational Outreach Chemistry Camp for Middle School Girls

Abstract: There continues to be a persistent, widespread gender gap in multiple STEM disciplines at all educational and professional levels: from the self-reported interest of pre-school aged students in scientific exploration, to the percentages of tenured faculty in these 10 disciplines, more men than women express an interest in science, a confidence in their scientific abilities, and ultimately more men than women decide to pursue scientific careers. Reported herein is an intensive outreach effort focused on address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 50 publications
1
66
0
2
Order By: Relevance
“…Países. Los trabajos seleccionados han sido desarrollados en 13 países diferentes (Tabla 3) entre los que destacan Estados Unidos (17), Israel (6), Portugal (3) y Alemania (2). Además de los países citados, se encontró un trabajo en: Turquía, Nueva Zelanda, Malasia, España, Dinamarca, Inglaterra, Canadá, Eslovenia y Eslovaquia.…”
Section: Países Etapas Educativas Disciplinas Científicas Y Contextunclassified
See 1 more Smart Citation
“…Países. Los trabajos seleccionados han sido desarrollados en 13 países diferentes (Tabla 3) entre los que destacan Estados Unidos (17), Israel (6), Portugal (3) y Alemania (2). Además de los países citados, se encontró un trabajo en: Turquía, Nueva Zelanda, Malasia, España, Dinamarca, Inglaterra, Canadá, Eslovenia y Eslovaquia.…”
Section: Países Etapas Educativas Disciplinas Científicas Y Contextunclassified
“…Emociones, motivación y actitudes -Incrementa el interés y la motivación por aprender ciencias (1,4,6,8,10,11,16,17,23,26,27,33,37). -No mejora el interés por las ciencias del alumnado (15,35).…”
Section: Referidas a Implicaciones Educativasunclassified
“…Generally, out-ofschool activities have a strong influence on student interest in science over time (Simpkins et al 2006). For many such events, participants reported that they enjoyed and learned most from hands-on activities (Laine et al 2017;Levine et al 2015). Examining student attitudes helps to explain the impact that out-of-school activities can generate.…”
Section: ; Ngss Lead States 2013; Organisation For Economicmentioning
confidence: 99%
“…More structured nature-related experiences, including urban community gardening projects, school-based gardening projects, and outdoor classrooms, have also been used to foster positive attitudes toward science and, in some cases, higher science achievement (Berezowitz, Bontrager, & Schoeller, 2015;Education & Roundtable, 2000;Fusco, 2001;Klemmer, Waliczek, & Zajicek, 2005;Mittelstaedt, Sanker, & VanderVeer, 1999;Williams, Brule, Kelley, & Skinner, 2018). Some STEM camps have also been found to improve both science attitudes and achievement (Bischoff, Castendyk, Gallagher, Schaumloffel, & Labroo, 2008;Gibson & Chase, 2002;Hayden, Ouyang, Scinski, Olszewski, & Bielefeldt, 2011;Knox, Moynihan, & Markowitz, 2003;Levine, Serio, Radaram, Chaudhuri, & Talbert, 2015;Markowitz, 2004). For example, students enrolled in the Summer Science Academy program at the University of Rochester reported more confidence in their science abilities, higher motivation to pursue a science career, and better performance in their science classes (Knox et al, 2003).…”
Section: Optional Science Experiences Motivation and Achievementmentioning
confidence: 99%